2005
DOI: 10.1620/tjem.206.99
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Habits before and during Menses in Japanese Women of Climacteric Age: A Population Based Study

Abstract: A good deal of data are available on the bowel habits of pre-climacteric females during menstruation. Few studies have examined the same subject in females of climacteric age but who are still menstruating, so the present study was undertaken to examine the bowel habits in menstruating females in this age group. Subjects (n = 246) were residents of a city in northern Japan, aged from 45 to 55 years old and who were still menstruating. Their every-day state of defecation and fecal characteristics were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
4
1
1
Order By: Relevance
“…The frequency of this report in the present study (20%) is lower than in a previous study where approximately one-third of females reported some change in stool consistency during menstruation [16]. However, the results of the present study differ from those of a Japanese study that found immediately before menstruation, in constipated women, feces to become harder and looser in 22.1 and 13.7%, respectively, compared with 8.7 and 9.5% in normal women [17].…”
Section: Discussioncontrasting
confidence: 99%
“…The frequency of this report in the present study (20%) is lower than in a previous study where approximately one-third of females reported some change in stool consistency during menstruation [16]. However, the results of the present study differ from those of a Japanese study that found immediately before menstruation, in constipated women, feces to become harder and looser in 22.1 and 13.7%, respectively, compared with 8.7 and 9.5% in normal women [17].…”
Section: Discussioncontrasting
confidence: 99%
“…These were evident in our study as being overweight/obese, less physical exercise, meat-based diet, and poor sleep quality were found to contribute significantly to CC. Moreover, we found that women in premenopausal period or with no delivery history appeared to be more likely to suffer from constipation, which might be associated with the fluctuations in female sex hormones and emotions [26,27]. We also observed that, compared with manual workers, non-manual workers tended to have a higher risk for CC.…”
Section: Discussionmentioning
confidence: 89%
“…Change in bowel movement across the menstrual cycle is well documented in Europe and the USA [12][13][14][15][16], but few studies have been undertaken using the Japanese population [17]. Furthermore, chronological associations between bowel habits and menstruation have not been determined Table 1.…”
Section: Introductionmentioning
confidence: 99%